Redes de interações transfronteiriças entre os municípios de Pato Bragado (Paraná – Brasil) e Nueva Esperanza (Canindeyú – Paraguay) - Kammer, Aline (2020)
This dissertation deals with the networks of cross-border interactions established in a Brazilian-Paraguayan border area, comprising the municipalities of: Pato Bragado, located in the extreme west of the state of Paraná - Brazil and Nueva Esperanza, located in the east of the Department of Canindeyú - Paraguay. In the border segment delimited for the study, the international limit between the two countries is old and was drawn over the Paraná River, a limit considered an obstacle to the crossing between Brazil and Paraguay. However, this characteristic was altered, notably after the construction of the Itaipu Hydroelectric Plant Reservoir in 1982. Thus, from an obstacle limit, the limit became porous, a fact that contributed to the establishment of networks of daily cross-border interactions of different natures, between municipalities. Knowing about these everyday networks, caused by flows that permeate the territorial limits of Brazil and Paraguay, we raise the following question, what are the reasons and the underlying logic that lead borderers to establish networks of cross-border interactions between Pato Bragado and Nueva Esperanza? To answer this question, we set out the objective of identifying and analyzing the typology of cross-border interaction networks established between these border municipalities, starting in 1982. For the study, we adopted the qualitative research methodology, with the application of interviews to the promoters of cross-border interactions, thus seeking greater contact with the border dynamics experienced in these municipalities. The interactions established in this border segment occur without national states, there is no legality in the collective pass, nor is there any sanitary or customs inspection on that border. However, this does not prevent these networks from happening on a daily basis. Thus, it was observed that the networks established from Nueva Esperanza to Pato Bragado are provided by the profound asymmetries found in rural communities located in the eastern periphery of the Paraguayan municipality, one form of (r) existence of these frontiers. The networks of cross-border interactions that leave from Pato Bragado to Nueva Esperanza, are linked to economic activities focused on agriculture in the municipality, which is also the scene of deep agrarian conflicts, precisely caused by the advance of Brazilian migrations over the decades. In addition to the material interactions, the networks established in this border area connect families, acquaintances and friends, who, coming and going across borders, take with them customs, culinary and beliefs, forging in this border segment unique identity traits, which form a rich cross-border territoriality.